Automatización inteligente en la gestión de la comunicación - Cesibel Valdiviezo-Abad; Tiziano Bonini (Doxa Comunicación, 2019)
New technologies have allowed the development of the industry, transforming it from 1.0 to the current, called 4.0 industry, which sees a rapid growth by the penetration of artificial intelligence and its various technologies that promise to surprise us all and invade the market and transform the world. Many of these technologies go hand in hand with intelligent automation that projects a large scale transformation. Faced with this metamorphosis, in this article deepens on the intelligent automation and in a special way in the management of the communication of the organizations, reviewing the existing bibliography and deepening on it. In conclusion, we propose a much more clarified state of the question and a contribution to the scarce bibliography referring to the subject of study that can serve as a connector between the aforementioned theories and a projection of automation in the field of communication.